(untitled) (Journal of the Bangladesh Agricultural University, 2016)
The objectives of this research study are to identify and measure the impact of the factors on brinjal production and to calculate the profit of brinjal production. Primary data collection was carried out at three villages of Islampur Upazila under Jamalpur district. Cobb-Douglas production function was applied to determine the effects of inputs on brinjal production. Human labor, seed cost, MP cost and pesticides have significant impact on brinjal production. The most important factor for variation in costs as identified was human labor and chemical fertilizers cost. Net return and cash margin of brinjal production were BDT 303,358 and BDT 345,415 per ha, respectively while the profit per Kg was BDT 6.63.Thus, Brinjal is a highly profitable enterprise. This study also identified some problems faced by farmers for producing brinjal like insects affect, lack of capital, lack of quality seed, lack of storage facilities, marketing problems. Thus more research and extension service can be adopted to solve the problems in order to increase production and ensure the nutritional food value in Bangladesh. J. Bangladesh Agril. Univ. 14(1): 113-118, June 2016